2014
DOI: 10.1371/journal.pone.0091826
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Microsatellite Markers for the BBCC Oryza Genome (Poaceae) Using High-Throughput Sequencing Technology

Abstract: Wild species of Oryza are extremely valuable sources of genetic material that can be used to broaden the genetic background of cultivated rice, and to increase its resistance to abiotic and biotic stresses. Until recently, there was no sequence information for the BBCC Oryza genome; therefore, no special markers had been developed for this genome type. The lack of suitable markers made it difficult to search for valuable genes in the BBCC genome. The aim of this study was to develop microsatellite markers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
4
5
0
Order By: Relevance
“…The remaining markers were not tried for PCR optimization as 70 SSR markers were considered enough for crossspecies amplification analysis compared with other earlier reports. The range of such successful SSR amplification rate in the present studies is similar to the result reported by other researchers (Wang et al 2014;Zheng et al 2013).…”
Section: Selection Of Ssr Markers and Genotypingsupporting
confidence: 92%
See 3 more Smart Citations
“…The remaining markers were not tried for PCR optimization as 70 SSR markers were considered enough for crossspecies amplification analysis compared with other earlier reports. The range of such successful SSR amplification rate in the present studies is similar to the result reported by other researchers (Wang et al 2014;Zheng et al 2013).…”
Section: Selection Of Ssr Markers and Genotypingsupporting
confidence: 92%
“…Since the SSR markers were designed using Nipponbare genome database and randomly selected from the 12 chromosomes covering the whole genome of rice, occurrence of ascertainment bias in the present study was avoided (Gao et al 2005). The cross-species amplification of SSR markers across the 18 rice genotypes which was estimated as the total number of SSR markers amplified in a particular genome type was ranged from 38.90% (RM280 and RM447) to 100% (RM490, RM318, RM279, RM18877 and RM20033, RM19303) with an average of 76.58% which is corroborated to the other reports (Wang et al 2014;Alexander et al 2018;Hernández et al 2001;Gupta et al 2003); this range was found to be higher as compared to the Melilotus with 61.40% (Yan et al 2017), Paspalum with 61% (Wang et al 2006), Siberian wildrye with 49.11% (Zhou et al 2016) and Cucumis with 12.70% (Fernandez-Silva 2008). Such differences in the rate of cross-species transferability could be explained by genetic relatedness and PCR primers used (Wang et al 2006).…”
Section: Cross-transferability Of Ssr Markers Across the Genomessupporting
confidence: 89%
See 2 more Smart Citations
“…Whole‐genome SSR detection has been reported in plants such as Oryza minuta and Or. punctata (Wang et al ., ), Sesamum indicum (Wei et al ., ), and Ziziphus jujuba (Xiao et al ., ) and in 30 marine animals (Jiang et al ., ), six species of birds (Huang et al ., ), six species of bovids (Qi et al ., ), Apis cerana (Liu et al ., ) and Tribolium castaneum (Demuth et al ., ). The SSRs in coding sequences (CDs) of 25 insect species have been identified and comparatively analyzed (Behura & Severson, ).…”
Section: Introductionmentioning
confidence: 99%